Glucocorticoid iontophoresis for Achilles tendon enthesitis in ankylosing spondylitis: significant response documented by power Doppler ultrasound - Ozgocmen, S; Kiris, A; Ardicoglu, O; Kocakoc, E; Kaya, A (Springer, 2005)
[Abstract Not Available]
Keywords: Spondyloarthropathies; Dexamethasone